Indo-Russian Economic Engagement: Legacy Issues, Dynamic Shifts, and Possibilities for the Future - Abhijit Mukhopadhyay (Vestnik MGIMO-Universiteta)
The economic relationship between India and Russia has been limited and faced various challenges historically. However, changing geopolitical and geoeconomic situations have created new opportunities while also presenting challenges and risks. This paper aims to analyse the legacy issues and dynamic shifts in international trade and order that are currently taking place. The article explores the ongoing transformation of Indo-Russian economic engagement and proposes possible means for moving forward. The existing advantages of both countries in the areas of trade and investment are also outlined.Assuming a resolution to the Russian Special Military Operation in Ukraine, the paper proposes an economic roadmap for continuing the recent momentum in the trade and economic relationship between Russia and India. The first step is to strengthen bilateral trade in existing priority export sectors of both countries. This can be followed by deeper cooperation in oil, civilian nuclear energy, and defence sectors. The introduction of rupee-rouble trade, even partially, could significantly boost these efforts. The paper also advocates for involving the private sector in these efforts by adopting a proactive approach by both governments.By combining immediate efforts with long-term geopolitical maneuvers on both sides and an early resolution of the Russian Special Military Operation in Ukraine, it is possible to push bilateral trade and investment levels onto a sustainable growth path in the future. The paper argues strongly for this approach.